Student-Based Evaluation of an Events Management Textbook for Instructional Material Quality Assurance - Glory Ann Karen C Caldingon; Nollie Boy D Jerson (Indonesian Journal of Education Research (IJoER), 2026)
Purpose of the study: This study evaluated a faculty-prepared Events Management textbook as an instructional material and identified evidence-based priorities for revision. The main objective was to generate practical revision directions that can improve the textbook’s instructional value in hospitality and tourism education. Methodology: A quantitative descriptive evaluation design was used among 152 Bachelor of Science in Hospitality Management and Bachelor of Science in Tourism Management students of Kalinga State University who had completed the course and used the textbook. Data were gathered through an adapted instructional material evaluation questionnaire with Likert-scale indicators and a revision recommendation checklist. Weighted mean, frequency, percentage, ranking, and a maintain-improve priority matrix were used to analyze the data. Main Findings: Students evaluated the textbook positively in physical features (M = 3.47), textbook parts (M = 3.48), overall evaluation (M = 3.49), and satisfaction (M = 3.52). The strongest areas suggest that the textbook is generally usable, organized, and engaging, particularly in lesson overview, readability, content quality, and relevance to learning. However, the lower-scoring indicators show clear revision needs in conversational tone, activity manageability, industry alignment, user instructions, visual appeal, delivery mode, and digital learning support. Educationally, the findings indicate that the textbook should be retained as a core learning resource but revised through a quality assurance cycle that connects student feedback with instructional design improvement. Novelty/Originality of this study: The study contributes a localized instructional material evaluation of an Events Management textbook and converts student assessment into a structured decision tool for revision. Its originality lies in combining textbook evaluation, student feedback, CIPP-informed quality assurance, ADDIE evaluation, ARCS satisfaction, and a priority matrix for instructional material improvement.